Mentoring Preachers and Quran Teachers to Strengthen Religious Moderation in the Border Region of Gorontalo–North Sulawesi - Muhammad Zainul Arifin; Basri; Ahmad Zaenuri; Nursodik (LP2M of Institute for Research and Community Services - UIN Walisongo, 2024)
Border areas are often associated with the complexity of identities, vulnerability to conflicts, and low security levels. This study aims to assist residents in border areas with diverse social, cultural, and religious differences. The selected areas are Gorontalo, which has a strong Islamic identity, and North Sulawesi, which is predominantly Christian. The study focuses on preachers and Quran teachers, as they hold a central role in conveying religious messages. The research method used is the Community Based Research (CBR) model with a descriptive approach. The results of the study found that religious moderation support through the internalization of moderate Islamic values, such as tolerance, rejection of violence, national commitment, and recognition of local traditions, successfully enhanced the understanding of religious moderation, although the increase was relatively small. Changes before and after mentoring, from understanding to a very understanding level of 10%. Understanding of moderation will be more optimal if mentoring activities are carried out continuously through formal and non-formal activities. This study recommends that religious moderation activities in formal forms need to receive non-formal mentoring in the form of implementing moderation values in everyday life so that they have relatively large potential in forming moderate attitudes in society's religion.